Pengaruh Storytelling, WOM, dan Brand Awareness Terhadap Keputusan Pembelian di Toko Murah Jenggawah - Nursaidah; Fadilatul Hasanah; Budi Santoso (Jurnal Manajemen DIVERSIFIKASI, 2026)
This research was conducted to determine the influence of storytelling, word of mouth and brand awareness on purchasing decisions at the Jenggawah Murah Shop. This research uses an associative quantitative method with a purposive sampling method of 90 respondents, using a questionnaire distributed via Google from to consumers of the Jenggawah Cheap Shop in Jember Regency. The data analysis used is the multiple linear regression test, partial test, and coefficient of determination test (R2). And the results of the analysis using SPSS 27 show that the three variables, namely storytelling, word of mouth, and brand awareness have a significant influence on purchasing decisions at the Jenggawah Cheap Shop. The results of the determination test (r2) were (41.6%) showing the large proportion or percentage contribution of the Storytelling, Word of Mouth and Brand Awareness variables to purchasing decisions. Meanwhile (58.4%) was contributed by other variables not included in this research, for example store atmosphere, location, price and so on.